Proliferation-apoptosis balance in Staphylococcus aureus chronically infected bovine mammary glands during involution - Andreotti, Carolina Soledad (2017)
The objective of this study was to determine whether Staphylococcus aureus chronic intramammaryinfection (IMI) influences expression of proteins related to regulation of proliferation and apoptosisprocesses and proliferation/apoptosis index during active involution in bovine mammary gland.Twenty-one Holstein non-pregnant cows in late lactation either uninfected or with chronic naturallyacquired S. aureus IMI were included in this study. Cows were slaughtered at 7, 14 and 21 d aftercessation of milking and samples for immunohistochemical analysis were taken. Protein expressionof Bcl-2, Bax, Fas and active caspase-3 in mammary tissue was significantly affected by chronic S.aureus IMI, all showing increased immunoexpression in S. aureus-infected quarters at all involutionstages. The percentage of apoptotic cells was increased by IMI in both mammary parenchyma andstroma, and the percentage of parenchymal and stromal cell proliferation was also increased. Theproliferation/apoptosis ratio was significantly increased by IMI only in stromal cells. This imbalanceto favour proliferation in S. aureus-infected mammary quarters could be one of the underlying causesthat induce aberrant involution with permanence of nonsecretory tissue and increase of stromalcomponents.